Utility of laser-cut covered self-expandable metal stents for unresectable malignant distal biliary obstruction: a single-center experience - Marui, Saiko; Uza, Norimitsu; Yamazaki, Hajime; Ota, Sakiko; Nakamura, Takeharu; Yoshida, Hiroyuki; Okada, Hirokazu; Hirano, Tomonori; Kuwada, Takeshi; Sogabe, Yuko; Tomono, Teruko; Matsumori, Tomoaki; Morita, Toshihiro; Nishikawa, Yoshihiro; Tsuda, Motoyuki; Maruno, Takahisa; Shiokawa, Masahiro; Kodama, Yuzo; Seno, Hiroshi (Endoscopy, 2020)
Background Few reports have evaluated the effectiveness of laser-cut, covered, self-expandable metal stents (LC-CSEMS) for unresectable malignant distal biliary obstruction (MDBO) and whether reintervention is feasible after placement. We describe our experience with LC-CSEMS placement for unresectable MDBO.Methods Patients undergoing LC-CSEMS placement for unresectable MDBO from November 2014 to December 2018 were reviewed. Recurrent biliary obstruction (RBO), median time to RBO (TRBO), and reintervention were analyzed.Results 52 patients who underwent LC-CSEMS placement for unresectable MDBO were included in the analysis. The RBO rate was 15 % and the median TRBO was 445 days. Reintervention was attempted in nine patients and stent removal was successful in eight patients.Conclusions Our experience suggests the effectiveness of LC-CSEMS in patients with unresectable MDBO in terms of stent patency and feasibility of reintervention.